An 11-Item Measure of User- and Human-Centered Design for Personal Health Tools (UCD-11): Development and Validation - Witteman, Holly O; Vaisson, Gratianne; Provencher, Thierry; Chipenda Dansokho, Selma; Colquhoun, Heather; Dugas, Michele; Fagerlin, Angela; Giguere, Anik MC; Haslett, Lynne; Hoffman, Aubri; Ivers, Noah M; Légaré, France; et al. (JMIR Publications, 2021)
BackgroundResearchers developing personal health tools employ a range of approaches to involve prospective users in design and development. ObjectiveThe aim of this paper was to develop a validated measure of the human- or user-centeredness of design and development processes for personal health tools. MethodsWe conducted a psychometric analysis of data from a previous systematic review of the design and development processes of 348 personal health tools. Using a conceptual framework of user-centered design, our team of patients, caregivers, health professionals, tool developers, and researchers analyzed how specific practices in tool design and development might be combined and used as a measure. We prioritized variables according to their importance within the conceptual framework and validated the resultant measure using principal component analysis with Varimax rotation, classical item analysis, and confirmatory factor analysis. ResultsWe retained 11 items in a 3-factor structure explaining 68% of the variance in the data. The Cronbach alpha was .72. Confirmatory factor analysis supported our hypothesis of a latent construct of user-centeredness. Items were whether or not: (1) patient, family, caregiver, or surrogate users were involved in the steps that help tool developers understand users or (2) develop a prototype, (3) asked their opinions, (4) observed using the tool or (5) involved in steps intended to evaluate the tool, (6) the process had 3 or more iterative cycles, (7) changes between cycles were explicitly reported, (8) health professionals were asked their opinion and (9) consulted before the first prototype was developed or (10) between initial and final prototypes, and (11) a panel of other experts was involved. ConclusionsThe User-Centered Design 11-item measure (UCD-11) may be used to quantitatively document the user/human-centeredness of design and development processes of patient-centered tools. By building an evidence base about such processes, we can help ensure that tools are adapted to people who will use them, rather than requiring people to adapt to tools.